C Language Extension to Support Procedural-Parametric Polymorphism - Alexander I. Legalov; Pavel V. Kosov (Моделирование и анализ информационных систем)
Software development is often about expanding functionality. To improve reliability in this case, it is necessary to minimize the change in previously written code. For instrumental support of the evolutionary development of programs, a procedural-parametric programming paradigm was proposed, which made it possible to increase the capabilities of the procedural approach. This allows to extend both data and functions painlessly. The paper considers the inclusion of procedural-parametric programming in the C language. Additional syntactic constructions are proposed to support the proposed approach. These constructions include: parametric generalizations, specializations of generalizations, generalizing functions, specialization handlers. Their semantics, possibilities and features of technical implementation are described. To check the possibilities of using this approach, models of procedural-parametric constructions in the C programming language were built. The example in the article demonstrates the flexible extension of the program and support of multiple polymorphism.